Circulating MicroRNA is a Biomarker of Biliary Atresia - Zahm, Adam M. (2012)
The lack of reliable noninvasive diagnostic biomarkers of biliary atresia (BA) results in delayed diagnosis and worsened patient outcome. Circulating microRNAs (miRNAs) are a new class of noninvasive biomarkers with encouraging diagnostic utility. In this study we examined the ability of serum miRNAs to distinguish BA from other forms of neonatal hyperbilirubinemia. BA-specific serum miRNAs were identified using a microfluidic array platform and validated in a larger, independent sample set. The miR-200b/429 cluster was significantly increased in the sera of BA patients and has promising diagnostic clinical performance.